2012
DOI: 10.1021/jp212174b
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of High-Incident-Energy Kr and Xe from Ice: Evidence that a Major Channel Involves Penetration into the Bulk

Abstract: The scattering of high kinetic energy (1–6.5 eV) xenon and krypton atoms from ice was experimentally measured and theoretically modeled. The ice efficiently accommodates translational energy, but the extent to which the energy is quenched suggests the mechanism for the highest energies and near-normal incidence angles involves more than interaction with just the molecules at the ice surface. Simulations show that for these conditions the xenon penetrates into the selvedge. This penetration into the solid manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(50 citation statements)
references
References 32 publications
(63 reference statements)
5
45
0
Order By: Relevance
“…However, it also appears that the uptake rate is also less than for Kr, which has almost the same mass as CF 4 . The previous experiments 10 with Xe and Kr showed that the rate of embedding decreased with exposure. The rates of CF 4 embedding vs. exposure curves were linear for all of the energies and exposures used, but the amount of CF 4 embedded had not reached a value as large as for the longest exposures of the rare gases.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…However, it also appears that the uptake rate is also less than for Kr, which has almost the same mass as CF 4 . The previous experiments 10 with Xe and Kr showed that the rate of embedding decreased with exposure. The rates of CF 4 embedding vs. exposure curves were linear for all of the energies and exposures used, but the amount of CF 4 embedded had not reached a value as large as for the longest exposures of the rare gases.…”
Section: Introductionmentioning
confidence: 83%
“…For both Xe and Kr, the rate of implantation was directly related to the translational energy, and for a given energy, Xe embedded at a higher rate than the lighter Kr. 10,24 The amount embedded appeared to asymptotically approach a final value that was dependent on energy and mass.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations